2014
DOI: 10.1007/s12015-014-9522-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Adipose Stem Cells in Cranial Facial Surgery

Abstract: Craniofacial malformations, have devastating psychosocial implications for many adults and children and causes huge socioeconomic burden. Currently craniofacial defects require soft tissue transfer, bone grafting techniques or difficult procedures such as microvascular free flaps. Such tissues are often limited in quantity, their harvest causes secondary large donor site defects and they lack the capability to fully restore previous form and function. Stem cell technology is being utilised for various tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 97 publications
0
29
0
1
Order By: Relevance
“…Relative to bone marrow, the adipose tissue is a commonly used source of MSCs for oral/maxillofacial surgeons in bone tissue engineering [24]. The stromal vascular fraction of the adipose tissue is one of the commonly used sources of MSCs, and hence, an important tissue to regenerative medicine scientists and researchers [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to bone marrow, the adipose tissue is a commonly used source of MSCs for oral/maxillofacial surgeons in bone tissue engineering [24]. The stromal vascular fraction of the adipose tissue is one of the commonly used sources of MSCs, and hence, an important tissue to regenerative medicine scientists and researchers [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, human adipose-derived stromal cells (hADSC) are often the choice of cell source for transplantation, in cell-based therapy, such as burn wound healing (12)(13)(14)(15)(16)(17). In addition, several studies have demonstrated that growth factors secreted by such cells are involved in angiogenesis and injury healing (18)(19)(20)(21)(22), yet a 3D scaffold for expansion and delivery of such cells is still considered to be a largely unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The current available treatments for RIF are limited and demanding including pharmacotherapy, hyperbaric oxygen therapy, and laser therapy. [16][17][18] These adult derived stem cells have the ability to self populate and differentiate into multiple cell types including the bone, cartilage, and adipose tissue. [3][4][5] Autologous fat transfer or lipotransfer for the restoration of soft tissue defects and scar reversal is a commonly utilized reconstructive and cosmetic surgical technique.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Lipotransfer has also populating the regenerative medicine literature as it has shown to contain an adult stem cell population, known as adipose derived stem cells (ADSCs). [16][17][18] These adult derived stem cells have the ability to self populate and differentiate into multiple cell types including the bone, cartilage, and adipose tissue. Although the mechanism by which the lipotransfer reverses the fibrosis is unclear, current research is focusing on establishing the effect of the ADSCs within the lipotransfer on several fibrotic conditions.…”
mentioning
confidence: 99%